Monitoring the systemic human memory B cell compartment of melanoma patients for anti-tumor IgG antibodies. - Amy E Gilbert; Panagiotis Karagiannis; Tihomir Dodev; Alexander Koers; Katie Lacy; Debra H Josephs; Pooja Takhar; Jenny L C Geh; Ciaran Healy; Mark Harries; Katharine M Acland; Sarah M Rudman; et al. (PLoS ONE)
Melanoma, a potentially lethal skin cancer, is widely thought to be immunogenic in nature. While there has been much focus on T cell-mediated immune responses, limited knowledge exists on the role of mature B cells. We describe an approach, including a cell-based ELISA, to evaluate mature IgG antibody responses to melanoma from human peripheral blood B cells. We observed a significant increase in antibody responses from melanoma patients (n = 10) to primary and metastatic melanoma cells compared to healthy volunteers (n = 10) (P<0.0001). Interestingly, we detected a significant reduction in antibody responses to melanoma with advancing disease stage in our patient cohort (n = 21) (P<0.0001). Overall, 28% of melanoma patient-derived B cell cultures (n = 1,800) compared to 2% of cultures from healthy controls (n = 600) produced antibodies that recognized melanoma cells. Lastly, a patient-derived melanoma-specific monoclonal antibody was selected for further study. This antibody effectively killed melanoma cells in vitro via antibody-mediated cellular cytotoxicity. These data demonstrate the presence of a mature systemic B cell response in melanoma patients, which is reduced with disease progression, adding to previous reports of tumor-reactive antibodies in patient sera, and suggesting the merit of future work to elucidate the clinical relevance of activating humoral immune responses to cancer.